2009
DOI: 10.1111/j.1365-2702.2008.02600.x
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Planning of Stroke Patients: the Relatives’ Perceptions of Participation

Abstract: Clinicians should give more attention to the altered situation of stroke patients' relatives when planning for continuing care and when setting postdischarge goals for the patients. The professionals need to develop strategies to involve relatives in sharing information, goal-setting and needs assessment in discharge planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
(43 reference statements)
5
28
0
Order By: Relevance
“…The relatives in our study expected more information from the reablement team than what was given. These findings are confirmed by several researchers,10,12,16,28,29 who argue that how the role as the relative in health care is handled is strongly associated with the opportunity to obtain information. Studies by Glendinning et al19 and Wilde and Glendinning2 revealed that family caregivers felt more confident in their caring responsibilities when information about the management of daily routines was passed on from the reablement team and when advice related to their own needs was given.…”
Section: Discussionsupporting
confidence: 66%
“…The relatives in our study expected more information from the reablement team than what was given. These findings are confirmed by several researchers,10,12,16,28,29 who argue that how the role as the relative in health care is handled is strongly associated with the opportunity to obtain information. Studies by Glendinning et al19 and Wilde and Glendinning2 revealed that family caregivers felt more confident in their caring responsibilities when information about the management of daily routines was passed on from the reablement team and when advice related to their own needs was given.…”
Section: Discussionsupporting
confidence: 66%
“…26,27 Breakdowns in communication are common when patients are discharged from one setting to another, such as from the hospital to home. 28 Because family members and friends often bridge settings alongside patients, 26,29 timely access to accurate information about the patient's health and discharge plan could improve transitional care 30 and help avert risky or redundant diagnostic procedures when a patient is incapacitated and unable to communicate.…”
Section: Capturing and Executing Patient Preferences For Familymentioning
confidence: 99%
“…Many people with chronic and disabling conditions co-manage or delegate health management activities to others. 31,32 However, family members and close friends are often not aware of patients' specific health issues, treatment recommendations, or care goals and consequently may not know how to best support lifestyle and medication treatment regimen adherence 29,32,33 or decision-making preferences. 34,35 Consumer health information technology is increasingly being used to engage patients in chronic and preventive care.…”
Section: Capturing and Executing Patient Preferences For Familymentioning
confidence: 99%
“…1,2 Almost 8 million older adults with significant disabilities live in the community with help from family and unpaid caregivers (family caregivers). 3,4 Older adults' family caregivers not only provide most assistance with everyday activities 3,5 but also help with a range of health care activities, such as physician visits, 6,7 transitions between settings of care, 8,9 medical decisions, 10,11 and medical tasks, such as injections, medication management, and wound care. 12 Because family caregivers are not systematically identified or routinely assessed in health care delivery, 1315 little is known about the degree to which they assist with health care activities or about the nature of caregiving-related effects they may experience.…”
mentioning
confidence: 99%